MANAGING SOVEREIGN CREDIT RISK IN BOND PORTFOLIOS - Bruder, Benjamin; Hereil, Pierre; Roncalli, Thierry (Journal of Advanced Studies in Finance; Vol 3 No 1 (2012): JASF Volume III Issue 1(5) Summer 2012, 2012)
With the recent development of the European debt crisis, traditional index bond management has been severely called into question. We focus here on the risk issues raised by the classical market-capitalization weighting scheme. We propose an approach to properly measure sovereign credit risk in a fixed-income portfolio. For that, we assume that CDS spreads follow a SABR process and we derive a sovereign credit risk measure based on CDS spreads and duration of portfolio bonds. We then consider two alternative weighting methods which are fundamental indexation and risk-based indexation. Fundamental indexation is based on GDP indexation whereas risk-based indexation uses a risk budgeting approach based on our sovereign credit risk measure. We then compare all these methods in terms of risk, diversification and performance. We show that the risk budgeting approach is the most appropriate scheme to manage sovereign credit risk in bond portfolios and gives very appealing results with respect to active management of bond portfolios.